“COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) AND TEAM PAIR SOLO (TPS) TECHNIQUES FOR HIGH AND LOW STUDENTS’ CREATIVITY IN WRITING NARRATIVE TEXT” - Wati, Dian Reftya (English Education: Jurnal Tadris Bahasa Inggris, 2015)
This study was investigated the effectiveness of cooperative learning namely, CIRC and TPS Techniques for High and Low Students’ Creativity in Writing Narrative Text. The objects of this study were conducted at the tenth graders the samples of the research were from two classes, each class consisting of 24 students. Each class was divided into two groups based on their level of creativity (high and low). The data were analyzed by using factorial design 2x2 of ANOVA test. The result of the study showed that: (1) CIRC technique is significance for high students’ creativity in learning teaching writing, (2) TPS is significance for high students’ creativity in teaching writing, (3) CIRC technique is significance for low students’ creativity in teaching writing, (4) TPS is significance for low students’ creativity in teaching writing, (5) there is an interaction among teaching techniques, students’ creativity and writing